Dietary intake pattern of lactating mother and under five children in selected districts of southern Bangladesh (Bangladesh Journal of Nutrition, 2018)
Food diversity is an important aspect of a healthy diet that reflects the various sources of nutrients that are consumed. Consumption of various food groups is used as a proxy indicator to assess the overall dietary intake and micro nutrient adequacy of studied population. The present study was undertaken to assess the dietary intake pattern of under-five children and lactating women from five upazilas of Satkhira, Khulna and Barisal districts, the most impoverished regions of southern Bangladesh. The study was cross-sectional in design where lactating (129) and under-five children (162) were selected as the target population. A two stage cluster sampling was used and information on food consumption was collected using a 24-hour dietary recall. The lion portion of lactating women’s diet was from plant source (560g) whereas animal sources contributed insignificant portion (67g). For lactating women energy intake fulfilled less than half of the RNI (41%) while protein and carbohydrate intake fulfilled almost half of the RNI (51%and 48% respectively). Fat intake was found severely low, fulfilling 11% of RNI. In under five children except protein all the macronutrient intake was considerably low. Protein intake fulfilled 98% and 107% of RNI for children of 6-23months and 24-59 months respectively. In case of micronutrients only vitamin C fulfilled above 101% of RNI for lactating mother while no other micronutrient fulfilled half of the RNI. In under five children almost half of RNI was fulfilled for vitamin A, thiamine, riboflavin, vitamin B6 and vitamin C. Findings of the present study revealed that the diet of lactating mother and under five children in southern part of Bangladesh is inadequate both in quantity and quality.Bangladesh J. Nutr. Vol. 28-31, December 2018, P: 25-31